Peran Perempuan Pedagang Dalam Meningkatkan Kesejahteraan Ekonomi Keluarga Di Desa Bua Kecamatan Tellulimpoe Kabupaten Sinjai - Nurliana Nurliana; Anwar Ramli; Darman Manda (Phinisi Integration Review, 2022)
Women generally have a dual role, namely as house wives and breadwinners. As a housewife, you are required to be able to complete family work. Meanwhile, as breadwinners, women are required to work in order to earn income to meet the daily needs of their families. This study aims to I) Find out how the role of women traders in improving the economic welfare of the family in Bua Village, Tellulimpoe District, Sinjai Regency. II) Knowing the reasons that encourage women to work as traders in improving the economic welfare of the family in Bua Village, Tellulimpoe District, Sinjai Regency. This type of research is classified as qualitative research. In this study, the informants were 6 people. This research uses observation, interview, and documentation techniques. The results of the study show that: I) Women with a profession as traders can improve the economic welfare of the family. They are not only skilled in the domestic sphere, but also in the public sphere. Women with their abilities are able to help families get out of poverty. II) There are four factors or reasons why women trade, namely the independence factor, the capital factor, the family factor and the coercive factor